(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Yartsev S. A. Keywords: business communication, resume, communicative task, communicative situation, document, self presentation. The article makes an attempt to define how much the information about education mentioned by the applicant in his resume corresponds to the communicative task he needs to solve; in what degree the fullness and clearness of the information depends on such role features of the writer applicant as his age, gender and professional occupation. The profession of the applicant turns out to be the most influential factor. Moreover, the questions in the resume form are found to be too common and not helping the reader of the resume to form the true image of the applicant.